Mikkel Bunkenborg, Morten Nielsen & Morten Axel Pedersen: Collaborative Damage - An Experimental Ethnography of Chinese Globalization - Lund, Christian (Tidsskriftet Antropologi, 2024)
Anmeldelse af Mikkel Bunkenborg, Morten Nielsen & Morten Axel Pedersens 'Collaborative Damage - An Experimental Ethnography of Chinese Globalization'